Restriction of HIV-1 Infection in Sickle Cell Disease Trait - Kumari, Namita; Khan, Javed; Ammosova, Tatiana; Ahmad, Asrar; Diaz, Sharmin; Rana, Sohail; Nekhai, Sergei (Blood, 2017)
We recently showed that in Sickle Cell Disease (SCD), activation of anti-viral restriction factor SAMHD1 and NF-κB inhibitor, IkBα prevented ex vivo HIV-1 infection. SAMHD1 activation was due to its reduced phosphorylation by CDK2, whose activity was inhibited by reduced intracellular iron levels in SCD peripheral blood mononuclear cells (PBMC). We also found that a hazard ratio associated with HIV infection among 11,412 SCD trait subjects was 1.0% comparing to >2% HIV-1 infection among African-Americans in USA. We compared 9 HbAS HIV-1 infected individuals with 107 HbAA or HbAC HIV-1 infected individuals who were enrolled at Howard University clinic. While hemoglobin levels in these two groups were not significantly different, HIV-1 viral load was significantly lower in HbAS group as well the number of HIV-1 associated complications (Hospitalization) were reduced. In the present study, we analyzed ex vivo HIV-1 infection of SCD trait PBMC and determined the expression of iron and hypoxia-regulated host factors including HO-1, NFκB, IKK, IKBα that are implicated in HIV-1 replication. We also analyzed CDK2 activity, SAMHD1 phosphorylation and RNR2 expression in SCD trait PBMCs. One round HIV-1 infection was significantly reduced in in SCD trait PBMC. Expression of HO-1 and IKBα was upregulated in SCD trait whereas IKK and NF-κB expression was downregulated. While CDK2 activity and SAMHD1 phosphorylation were not changed, RNR2 expression was reduced. Expression levels of HIV-1 env and gag mRNA were significantly lower in HIV-1 infected SCD trait subjects. In the same patients, HO-1 and IKBα mRNA levels were upregulated comparing to HIV-1+ HbAA or HbAC subjects. Our findings suggest that HIV-1 infection might be deregulation in SCD trait and that iron metabolism and hypoxia might play a role in this deregulation. This work was supported by NIH Research Grants 1P50HL118006, 1R01HL125005, and 5G12MD007597. The content is solely the responsibility of the authors and does not necessarily represent the official view of NHLBI, NIMHD or NIH. No relevant conflicts of interest to declare.